Cancer of the Uterine Cervix - Franco Eduardo L; Duarte-Franco Eliane (BMC, 2004)
Abstract Health issue Cervical cancer is one of the most common malignant diseases of women; it is diagnosed in almost half a million women every year and half as many die from it annually. In Canada and other industrialized countries, its incidence has decreased due to cytology screening. However, invasive cases still occur, particularly among immigrant groups and native Canadian women. Although incidence of squamous cell carcinomas has decreased, the proportion of adenocarcinomas has increased because Pap cytology is ineffective to detect these lesions. Key findings In Canada, cervical cancer will cause an estimated 11,000 person-years of life lost. In most Canadian provinces, early detection is dependent on opportunistic screening. Primary prevention can be achieved through health education (sexual behavior modification) and vaccination to prevent infection from Human Papillomavirus (HPV). The initial results from vaccination trials are encouraging but wide scale use is more than a decade away. Data gaps and recommendations Most cases of cervical cancer occur because the Pap smear was either false negative, was not done or not done often enough. Appropriate recommendations and guidelines exist on implementation of cytology-based programs. However, most Canadian women do not have access to organized screening. Further research is needed to 1) evaluate automated cytology systems; 2) define appropriate management of precursor lesions and 3) deliver definitive evidence of HPV testing efficacy in long-term follow-up studies with invasive cancer as an outcome and 4) provide Canadian data to justify augmenting or modifying current programs to use HPV testing in secondary triage of equivocal Pap smears.